Управление излучением светодиода магнитным полем - Ирха, В.И. (Моделювання та інформаційні технології, 2010)
We detected the magnetic field influence on emission intensity of
LED. In transverse magnetic field the area of radiative recombination is displaced to
small-gap region of base of variband LED. It lead to a shifting of LED”s emission
spectrum to a low-energy range. In magnetic field the emission intensity decreases bеcause the injected charge carriers deviate to a surface, where the nonradiative
probability increases.